Abundant off-axis hydrothermal activity in the 29–30 ridge segment of the Southwest Indian Ridge: evidence from ferromanganese crusts - Yang, Xianhui; Tao, Chunhui; Liao, Shili (Frontiers in Earth Science, 2023)
The seafloor hydrothermal fields are mainly discovered by detecting the hydrothermal plume anomaly, but there are no effective means to investigate the inactive hydrothermal fields. Based on five ferromanganese crusts collected from the 29-30 ridge segment of the Southwest Indian Ridge, geochemical analysis was carried out to reveal the relationship between the ferromanganese crusts and nearby hydrothermal activities. It is found that the Co content and rare earth element content of ferromanganese crusts in this region are significantly lower than those of hydrogenetic crusts, and the material source discrimination diagram revealed that they have mixed hydrogenetic and hydrothermal origins. Among them, the sampling stations of three crusts are located within 2 km of the known hydrothermal fields(HFs), and these HFs are in an inactive state. Additionally, there may be unknown HFs near the sampling stations of two crusts, which have been confirmed by the results of the water column anomaly survey and seafloor photography survey in the area. The spatial frequency of hydrothermal activity in this study area reached 15 sites/100 km, which is significantly higher than other well-studied ridges with good survey levels. The control factors of hydrothermal activity in this area are diverse, including both magmatic-driven systems and tectonic-driven systems, which are related to their different tectonic environments. The results of this study suggest that a geochemical survey of ferromanganese crust samples can be used as a means of 2 investigating inactive seafloor hydrothermal activities and that the Southwest Indian Ridge has a high potential for hydrothermal activity research.